Entrepreneurship - Lazear, Edward P. (Journal of Labor Economics, 2005)
The theory below is that entrepreneurs must be jacks-of-all-trades who need not excel in any one skill but are competent in many. A model of the choice to become an entrepreneur is presented. The primary implication is that individuals with balanced skills are more likely than others to become entrepreneurs. Using data on Stanford alumni, the predictions are tested and found to hold. Those who have varied work and educational backgrounds are much more likely to start their own businesses than those who have focused on one role at work or concentrated in one subject at school.